PELATIHAN PEMBUATAN BROSUR SEBAGAI STRATEGI KOMUNIKASI PEMASARAN PADA PASAR BADUNG - Ni Made Rinayanthi; Putu Dian Yuliani Paramita (Sewagati, 2024)
The brochure creation training as a marketing communication strategy at Pasar Badung aims to enhance traders' ability to promote their products and services through effective and attractive printed media. Brochures are an important communication tool in marketing, providing clear information and stimulating consumer interest. This training focuses on teaching graphic design and persuasive content writing, which not only highlights the uniqueness of the products but also attracts the target market, including both tourists and local communities. Through this training, traders at Pasar Badung are equipped with skills to create aesthetically pleasing, informative, and market-appropriate brochures. Additionally, participants are trained in selecting appropriate distribution channels, both physically at the market location and digitally via social media to expand marketing reach. The expected outcome of this training is to enhance the image of Pasar Badung as a unique and appealing shopping destination, while also introducing local products in a more professional manner. With well-designed brochures, Pasar Badung can more effectively attract visitors and increase transaction volumes, ultimately contributing to local economic growth and the tourism sector in Bali. This training is a strategic step in supporting the development of traditional markets as part of Bali's sustainable creative economy.